Comprehensive investigations and simulation study on the mechanism of crack initiation and propagation of compressor blade's tenon. Issue 10 (3rd October 2022) - Xiao, Dingtian; Qing, Shan; Du, Shunlin; Xiao, Huaqiang; Wang, Tao; Zhao, Liang
Abstract: A systematic research on the fracture failure of the tenon of X20Cr13 blade has been carried out. This research consists of two parts: comprehensive analysis and simulation analysis. The fretting wear produces the failure source which leads to the occurrence and development of cracks. M23C6 carbides damage the continuity of matrix structure and create conditions for the initiation and propagation of cracks. The simulation analysis further confirmed that the stress at the root of blade tenon is too large and the possibility of failure caused by resonance is eliminated. Some constructive suggestions are put forward for this engineering problem.